2013
DOI: 10.1093/her/cyt071
|View full text |Cite
|
Sign up to set email alerts
|

Accessing sexual health information online: use, motivations and consequences for youth with different sexual orientations

Abstract: We examine reasons why youth of different sexual orientations look for sexual health information online, and what, if anything, they do with it. The Teen Health and Technology study involved online surveys of 5542 Internet users, ages 13 through 18 in the United States. Searching for sexual health information online was reported frequently and varied significantly by sexual orientation: from 19% of heterosexual youth to 78% of gay/lesbian/queer youth. The most common reasons youth look for sexual health inform… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
122
1
8

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 175 publications
(139 citation statements)
references
References 26 publications
8
122
1
8
Order By: Relevance
“…Research has demonstrated that LGBTI youth are more likely to struggle with issues of access to sexual health information and services and this may influence such a population in seeking information elsewhere, such as online interactive spaces (Knight et al 2014;Mitchell et al 2014). Constructs of sexuality in terms of being a 'top' or a 'bottom' have been explored by researchers interested in the sexual identification and practice of gay men, and attest to the complexities of identification that language and labelling practice imply in general (GrundyBowers, Hardy and McKeown 2015;Johns et al 2012;Kippax and Smith 2001;Matebeni and Msibi 2015;McGill and Collins 2014a;McGill and Collins 2014b;.…”
Section: Top/bottom Constructs Amongst Gay Men: Implications For Sexumentioning
confidence: 99%
See 3 more Smart Citations
“…Research has demonstrated that LGBTI youth are more likely to struggle with issues of access to sexual health information and services and this may influence such a population in seeking information elsewhere, such as online interactive spaces (Knight et al 2014;Mitchell et al 2014). Constructs of sexuality in terms of being a 'top' or a 'bottom' have been explored by researchers interested in the sexual identification and practice of gay men, and attest to the complexities of identification that language and labelling practice imply in general (GrundyBowers, Hardy and McKeown 2015;Johns et al 2012;Kippax and Smith 2001;Matebeni and Msibi 2015;McGill and Collins 2014a;McGill and Collins 2014b;.…”
Section: Top/bottom Constructs Amongst Gay Men: Implications For Sexumentioning
confidence: 99%
“…According to research, many closeted gay men often experience a sense of shame through internalised homophobia and may also feel fear about being 'outed' when seeking knowledge and information about sexual health practice (Emlet et al 2015). For many of these men, silencing or alternative means of accessing information may be adopted (Mitchell et al 2014) that do not guarantee effective strategies of combatting unsafe sex practice. The interface of internalised homophobia with seeking access to health services and other avenues for counselling and communication is a strong relationship that many gay men face (Weber-Gilmore, Rose and Rubinstein 2011).…”
Section: Being a Bottom And Access To Healthmentioning
confidence: 99%
See 2 more Smart Citations
“…Alternatively, since media and technology transcend the boundaries of physically distinct everyday environments, such as home and school, they may be conceptualised as creating an important microsystem within their own right. Adolescents increasingly turn to media and technology as a source of sociocultural information to guide their attitudes, beliefs and behaviours in a variety of domains (Lloyd, 2002;Mitchell, Ybarra, Korchmaros, & Kosciw, 2014), much in the same way they may have traditionally turned to family, teachers and peers (Strasburger & Wilson, 2002).…”
Section: Contextualising Developmentmentioning
confidence: 99%